Strategic Management and Good Governance Administration Affecting the Supplies Management Efficiency of the Offices of Non-formal and Informal Educational Promotion in Sakon Nakhon Province - Buadee, Tanyaporn; Aiyakorn, Samart; Udomkijmongkol, Chardchai (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Supplies management is important to management as a factor for success in achieving the organization’s vision (Vision) in both small organizations and large organizations. It is essential to have effective supply management. Therefore, workers must have qualifications and have direct knowledge, and the ability to deal with supplies to get the job done successfully and efficiently. Thus, The purposes of the research included the following: 1) To study the level of strategic management, good governance administration, and the supplies management efficiency of the Offices of Non-formal and Informal Educational Promotion in Sakon Nakhon Province, 2) to investigate the influences of strategic management and good governance administration on the supplies management efficiency of the Offices of Non-Formal and Informal Educational Promotion in Sakon Nakhon Province. Methodology: Obtained through stratified random sampling method, the sample group consisted of 283 personnel who were in charge of managing the supplies in the Offices of the Non-formal and Informal Educational Promotion in Sakon Nakhon Province. The tool used for data collection was a questionnaire and the statistics employed for data analysis were frequency, percentage, mean, standard deviation, and Multiple Regression, Analysis. Results: (1) The overall strategic management of the Offices of Non-formal and Informal Educational Promotion was at a high level. In a similar vein, the good governance administration of the Offices of Non-formal and Informal Educational Promotion was at a high level). In addition, the supply management efficiency of the Offices of Non-formal and Informal Educational Promotion, as a whole, was also at a high level. (2) These strategic management variables could be used jointly to correctly predict the level of the supplies management efficiency for 89.30 percent (R2Adj=.893) with statistical significance at the .05 level: strategy implementation (β=.403), strategy formulation (β=.274), environmental monitoring (β=.167), and strategy control and evaluation (β=.133). (3) Except for transparency and participation, these good governance administration variables could be used jointly to accurately predict the level of the supplies management efficiency for 89.70 percent (R2Adj=.897), at .05 statistical level of significance: responsibility/accountability (β=.304), morality (β=.241), rule of law (β=.232) and value for money (β=.131). Conclusion: The results indicate that the strategic management and good governance practices within the Offices of Non-formal and Informal Educational Promotion are highly efficient, significantly impacting the overall supply management effectiveness. Key factors such as strategy implementation, formulation, environmental monitoring, responsibility/accountability, morality, rule of law, and value for money play crucial roles in predicting and improving supply management efficiency, suggesting a strong correlation between strategic management and good governance practices with supply management outcomes.